Symptom clusters after chemoradiotherapy in discharged nasopharyngeal carcinoma patients - Li, Xiang; Fu, Gui-Fen; Huang, Yu-Ying; Jiang, Qing-Yu; Huang, Xiao-Yan; Zhang, Jin-Tao; Qu, Shen-Hong (Frontiers in Oncology, 2023)
Objective To investigate the incidence of complications and types of chemoradiotherepy induces symptom clusters in patients with nasopharyngeal carcinoma (NPC) who were first diagnosed after treatment and discharged from hospital. Methods After their discharge home, 130 NPC patients who had been treated with chemoradiotherapy were asked to complete a modified Chinese version of the Quality of Life Questionnaire–Head and Neck Module developed by the European Organization for the Research and Treatment of Cancer in the Head and Neck. Symptom clusters in patients were identified through exploratory factor analysis. Results The most serious symptoms for discharged NPC patients who had received chemoradiotherapy were dental problems, a sense of obstruction while swallowing, embarrassment in physical contact with family members and friends, difficulty in speaking with others, and embarrassment in public. The six symptom clusters identified through exploratory factor analysis were (1) painful eating, (2) social difficulties, (3) psychological disorders, (4) symptomatic shame, (5) teeth/throat injuries, and (6) sensory abnormalities. The total contribution rate of variance was 65.73%. Conclusion NPC patients who are treated with chemoradiotherapy can experience adverse symptom clusters that continue after discharge. Nurses should evaluate the patients’ symptoms before discharge and provide targeted health education services which would reduce the patients’ complications and improve the quality of life at home. Besides, medical staff should evaluate the complications in a timely and comprehensive manner and provide individualized health education for the affected patients to help them manage chemoradiotherapy side effects.